2015
DOI: 10.1186/s40643-015-0063-7
|View full text |Cite
|
Sign up to set email alerts
|

Fetal bovine serum: geographic origin and regulatory relevance of viral contamination

Abstract: The article aims to clarify an existing misunderstanding by the users of fetal bovine serum (FBS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 3 publications
0
28
0
2
Order By: Relevance
“…New Zealand only imports BSA from Australia [ 38 ] and is an exporter of BSA to other countries. These restrictions were implemented to prevent importation of bovine spongiform encephalopathy (BSE) prions [ 39 ], but do not address the risks of the importation of BVDV, and remains an area for both countries to address.…”
Section: A New Zealand and Australian Perspectivementioning
confidence: 99%
“…New Zealand only imports BSA from Australia [ 38 ] and is an exporter of BSA to other countries. These restrictions were implemented to prevent importation of bovine spongiform encephalopathy (BSE) prions [ 39 ], but do not address the risks of the importation of BVDV, and remains an area for both countries to address.…”
Section: A New Zealand and Australian Perspectivementioning
confidence: 99%
“…CHO cells are permissive to multiple types of viruses such as Adenovirus, Parainfluenza virus, Bovine respiratory syncytial virus, Vesicular stomatitis virus, Reovirus, and Bluetongue virus [14]. All the viruses listed above could be transmitted from either HEK-293 cells [11,12,13] or fetal bovine serum [8]. We believe there are unknown or undetected viruses existing in HEK-293 and bovine serum.…”
Section: Resultsmentioning
confidence: 99%
“…Serum is a potential source of contamination by viruses, mycoplasmas, and even prions. It has been reported that Bovine respiratory syncytial virus, Bovine viral diarrhea virus, Rabies virus, Vesicular stomatitis virus, Bluetongue virus, and Foot and mouth disease virus could be isolated from bovine serum [8]. To avoid contamination by potential infectious viruses from serum, retrovectors could be packaged in suspension HEK-293 cells cultured in a serumfree or CD medium.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to scientific disadvantages such as unknown exact composition, seasonal and geographical lot-to-lot variability (Baker, 2016b), and unintended interaction with test substances (Groothuis et al, 2015;Kramer et al, 2009), which can lead to unexpected or undesired outcomes, serious safety concerns for laboratory personnel in terms of endotoxins, mycoplasma and viral contaminants or prion proteins (Dormont, 1999;Wessman and Levings, 1999;Hawkes, 2015), as well as ethical concerns vine fetuses in the last third of their development, if it takes place on EU territory, is thus a procedure under the Directive because the serum is clearly used for scientific purposes and is extracted from a living animal. Therefore, the procedures would need to undergo a project review and authorization by a competent authority.…”
Section: Problems Of Fbs Usementioning
confidence: 99%